Association of dietary glycemic index and glycemic load with the risk of gestational diabetes mellitus: a systematic review and dose-response meta-analysis - Yu Zhang; Huanrong Feng; Xuefeng Li; Qiong Chen; Ruyue Shao; Chengli Wang; Yimeng Gao (Gynecological Endocrinology)
Objective To comprehensively assess the dose-response association between dietary glycemic index (GI) and glycemic load (GL) and gestational diabetes mellitus (GDM) risk.Methods PubMed, Embase, Cochrane Library, Web of Science, CNKI, WanFang, and VIP databases were searched up to May 29, 2024. Studies with at least three exposure categories were included. Dose-response analysis was also performed when covariates were adjusted in the included studies.Results Thirteen studies involving 39,720 pregnant women were included. A linear relationship was found between GI and the risk of GDM (χ2 = 4.77, Pnon-linearity = .0923). However, association was not significant (χ2 = 0.06, p = .8000). For every unit increase in GI (range 0–30), GDM risk increased by 0.29%. After adjusting for covariates, the linear relationship persisted (χ2 = 4.95, Pnon-linearity = .084) with no significant association (χ2 = 0.08, p = .7775). For GL, a linear relationship was also found (χ2 = 4.17, Pnon-linearity =.1245), but GL was not significantly associated with GDM risk (χ2 = 2.63, p = .1049). The risk of GDM increased by 0.63% per unit increase in GL. After covariate adjustment, a significant association was observed (χ2 = 6.28, p = .0122).Conclusion No significant association between GI and GDM risk was found. After adjusting for covariates, GL shows a significant association with GDM risk. Our findings emphasize the importance of considering dietary GL in managing the risk of GDM. Future research should continue to explore these relationships with standardized diagnostic criteria and robust adjustment for potential confounders.